Prevalence of human papillomavirus DNA and p16INK4a positivity in vulvar cancer and vulvar intraepithelial neoplasia: a systematic review and meta-analysis. Issue 4 (April 2023) - Li, Zhuang; Liu, Penglin; Wang, Ziying; Zhang, Zhaoyang; Chen, Zhongshao; Chu, Ran; Li, Guiju; Han, Qiuyue; Zhao, Yong; Li, Li; Miao, Jinwei; Kong, Beihua; et al.
Summary: Background: Human papillomavirus (HPV) DNA and p16 INK4a positivity have crucial roles in the pathogenesis of vulvar cancer and vulvar intraepithelial neoplasia. We aimed to examine the pooled prevalence of HPV DNA and p16 INK4a positivity in vulvar cancer and vulvar intraepithelial neoplasia worldwide. Methods: In this systematic review and meta-analysis, we searched PubMed, Embase, and the Cochrane Library databases for studies published between Jan 1, 1986, and May 6, 2022, that reported the prevalence of HPV DNA, or p16 INK4a positivity, or both, in histologically verified vulvar cancer or vulvar intraepithelial neoplasia. Studies on a minimum of five cases were included. Study-level data were extracted from the published studies. Random effect models were used to examine the pooled prevalence of HPV DNA and p16 INK4a positivity in both vulvar cancer and vulvar intraepithelial neoplasia, which were further investigated using stratified analyses by histological subtype, geographical region, HPV DNA or p16 INK4a detection method, tissue sample type, HPV genotype, publication year, and age at diagnosis. Additionally, meta-regression was applied to explore sources of heterogeneity. Findings: We retrieved 6393 search results, of which 6233 were excluded for being duplicates or after application of our inclusion and exclusion criteria. We also identified two studies from manual searches of references lists. 162 studies were eligible for inclusion in the systematic review and meta-analysis. The prevalence of HPV in vulvar cancer (91 studies; n=8200) was 39·1% (95% CI 35·3–42·9) and in vulvar intraepithelial neoplasia (60 studies; n=3140) was 76·1% (70·7–81·1). The most predominant HPV genotype in vulvar cancer was HPV16 (78·1% [95% CI 73·5–82·3]), followed by HPV33 (7·5% [4·9–10·7]). Similarly, HPV16 (80·8% [95% CI 75·9–85·2]) and HPV33 (6·3% [3·9–9·2]) were also the most two predominant HPV genotypes in vulvar intraepithelial neoplasia. The distribution of type-specific HPV genotypes in vulvar cancer among geographical regions was different, with HPV16 varying between regions, showing a high prevalence in Oceania (89·0% [95% CI 67·6–99·5]) and a low prevalence in South America (54·3% [30·2–77·4]). The prevalence of p16 INK4a positivity in patients with vulvar cancer was 34·1% (95% CI 30·9–37·4; 52 studies; n=6352), and it was 65·7% (52·5–77·7; 23 studies; n=896) in patients with vulvar intraepithelial neoplasia. Furthermore, among patients with HPV-positive vulvar cancer, p16 INK4a positivity prevalence was 73·3% (95% CI 64·7–81·2), compared with 13·8% (10·0–18·1) in HPV-negative vulvar cancer. The prevalence of double positivity for HPV and p16 INK4a was 19·6% (95% CI 16·3–23·0) in vulvar cancer and 44·2% (26·3–62·8) in vulvar intraepithelial neoplasia. Most analyses had large heterogeneity ( I 2 >75%). Interpretation: The high prevalence of HPV16 and HPV33 in vulvar cancer and vulvar intraepithelial neoplasia emphasised the importance of nine-valent HPV vaccination in preventing vulvar neoplasm. Additionally, this study highlighted the potential clinical significance of double positivity for HPV DNA and p16 INK4a in vulvar neoplasm. Funding: Taishan Scholar Youth Project of Shandong Province, China.